Peningkatan Sumber Daya Manusia pada Majelis Taklim Jamiyyatul Ummahat Jakarta Selatan - Heni Ani Nuraeni; Lany Polina (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2019)
The Council of Ta’lim is a non-formal educational institution managed by a community and contributes to the development of human resource particulary in terms of religious teaching. The research aims to study various activities carried out in the Council of Ta’lim of Jamiyyatul Ummahat South Jakarta toward the improvement of its human resources. This research applies qualitative methods using case study approach. Data were collected through observations, interviews, and documentation and then analyzed using Miles and Huberman’s interactive model analysis. The results showed that the human resources in the Council are improved through a number of activities, such as coaching activities for leaders and managers, trainings and educational competitions. These activities have indirectly contributed to the improvement of human resources as well as increased the community participation.